Russia's growth potential post-COVID-19 - Iikka Korhonen (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
This paper updates my earlier calculations on Russia's long-run growth potential using a standard growth accounting framework in which GDP growth depends on available labor, capital and efficiency in combining them, i.e. total factor productivity. Russia's economy has grown relatively slowly during the past decade, partly because of declining labor force. In my revised framework, growth recovers after the negative COVID-19 shock, but remains subdued as the working-age population continues to dwindle. Productivity growth remains lower than in the early 2000s, while average GDP growth settles at approximately 1.5% p.a.
urn:nbn:fi:bof-202107011317
Keywords: 330; Coronavirus; Produktionspotenzial; Wirtschaftswachstum; Russland